2020
DOI: 10.1007/s13201-020-1151-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of COD and Ammoniacal Nitrogen from dye intermediate manufacturing Industrial Wastewater using Fenton oxidation method

Abstract: The untreated wastewater from the dye industry having high ammoniacal nitrogen and chemical oxygen demand (COD) significantly pollutes the receiving water, such as a river, having major ill implications on the aquatic environment. The present study is undertaken to address this problem. It investigates the effectiveness of Fenton reagent in simultaneous treatment (removal) of ammoniacal nitrogen and COD present in the wastewater by varying the parameters like pH, concentration of Fe 2+ and H 2 O 2 and their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Further degradation of organic matter decelerated down due to complete consumption of [ • OH]. Additionally, some inorganic ions like chlorides, carbonates, bicarbonates, and bromides present or generated in degrading organic matter may alter the rate of reaction [15]. Similar experiments were performed by Maharaj et al [7] with synthetic wastewater and observed a maximum COD reduction of 70% at the reaction time of 360 min.…”
Section: Fenton Processmentioning
confidence: 53%
“…Further degradation of organic matter decelerated down due to complete consumption of [ • OH]. Additionally, some inorganic ions like chlorides, carbonates, bicarbonates, and bromides present or generated in degrading organic matter may alter the rate of reaction [15]. Similar experiments were performed by Maharaj et al [7] with synthetic wastewater and observed a maximum COD reduction of 70% at the reaction time of 360 min.…”
Section: Fenton Processmentioning
confidence: 53%
“…This is because, if there is not enough Fe 2+ , in the presence of excess H 2 O 2 hydroxyl radicals change form by scavenging and this causes a decrease in oxidation 27 . In case of excess H 2 O 2 , the following reaction occurs: 27‐29 normalH2normalO2+OHHO2+normalH2O Turbidity removal increased above 98% at a H 2 O 2 concentration higher than 3250 mg L −1 . TSS removal increased from 67.6% to 76.1% with an increase in H 2 O 2 concentration from 3000 to 4250 mg L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, γ-MnO 2 /AC showed a good degradation effect on the secondary biochemical effluent of printing and dyeing wastewater (72.45% COD removal in 120 min). Pani et al 52 investigated the effect of Fenton reagent in the simultaneous treatment (removal) of ammonia nitrogen and COD from wastewater by varying parameters such as pH, Fe 2+ and H 2 O 2 concentrations, and molar ratio. The experimental analysis showed that the removal of COD can reach 78.6% at a molar ratio of 1:3.…”
Section: Impact Of the Ph Value In Solutionmentioning
confidence: 99%